LEGAL STATUS OF ADOPTED CHILDREN IN THE CIVIL INHERITANCE LAW BASED ON ARTICLE 832 OF THE CIVIL LAW BOOK - Wulan Agustini; Gunawan Djajaputra (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Adoption of children based on Article 1 number 2 of Government Regulation Number 54 of 2007 concerning the Implementation of Adoption states that: "A legal act that diverts a child from the environment of power of parents, legal guardians, or other people who are responsible for the care, education and upbringing of children the child, into the adoptive parent's family environment. The rights of adopted children regarding property left by adoptive parents is an inheritance problem that occurs in many communities. Regarding inheritance rights that arise after a parent dies, there is a difference in the amount of inheritance obtained by adopted children and biological children. In fact, sometimes adopted children are still considered not part of the family, which in the end, the rights of adopted children are ignored. This does not rule out the possibility of problems such as the distribution of inheritance. The formulation of the problem in this study: (1) What is the legal position of adopted children in civil inheritance law based on Article 832 of the Civil Code? (2) What is the legal protection for adopted children in the distribution of inheritance? The research method used is normative legal research method. The primary legal materials used in this writing are the 1945 Constitution of the Republic of Indonesia and the Civil Code. The secondary legal materials are in the form of all legal publications which are not official documents. The tertiary legal materials used in this study are the Big Indonesian Dictionary and the Legal Dictionary. The results of the study show that the legal position of adopted children in civil inheritance law based on Article 832 of the Civil Code, namely the Civil Code does not specifically regulate the inheritance rights of adopted children, but they are entitled to a share through a will grant. The Civil Code only regulates the recognition of children out of wedlock. The Netherlands once regulated it in Staatsblad No. 129 of 1917 which applies to the Chinese group. Based on the Criminal Code there are restrictions in terms of making a will, namely regarding the size of the inheritance to be distributed to heirs which is called ligitime portie which is regulated in Articles 913-929 of the Criminal Code. Legal protection for adopted children in the distribution of inheritance according to Philipus M. Hadjon is divided into two, namely preventive legal protection and repressive legal protection. Preventive legal protection provides an opportunity for the child to submit objections or opinions before a government decision violates children's rights, the aim is to prevent violations of children's rights. Repressive legal protection is a legal protection for prosecution by the government whose purpose is to resolve disputes.